Unusual Cause of Gastrointestinal Bleeding in an Elderly Adult: Gastric Kissing Ulcers - Osman Yüksekyayla,; Ersin Batıbay,; Cumali Efe, (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Yüksekyayla O, Batıbay E, Efe C. Unusual cause of gastrointestinal bleeding in an elderly adult: Gastric kissing ulcers. Turk J Gastroenterol. 2024;35(5):421-422.